2004
DOI: 10.1081/jcmr-120027802
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Rapid Prescreening Magnetic Resonance Angiography of Peripheral Vascular Disease Prior to Cardiac Catheterization

Abstract: MRA prescreening in patients with PVD is an effective, novel adjunct to cardiac catheterization in selected patients that improves physician confidence and influences technical choices during coronary angiography from the femoral artery approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Magnetic resonance and fluoroscopy have been recommended to assist arterial puncture by a few authors, but only a paucity of data exists. 15,17,18,27 Our study has several limitations. We report on the experience of a limited number of high-volume physicians practicing at one institution, and whether our results will generalize is unknown.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Magnetic resonance and fluoroscopy have been recommended to assist arterial puncture by a few authors, but only a paucity of data exists. 15,17,18,27 Our study has several limitations. We report on the experience of a limited number of high-volume physicians practicing at one institution, and whether our results will generalize is unknown.…”
Section: Discussionmentioning
confidence: 94%
“…In this latter study, only in the subgroup analysis were significant differences observed, primarily in patients with a weak, palpable pulse or with a large leg circumference. Magnetic resonance and fluoroscopy have been recommended to assist arterial puncture by a few authors, but only a paucity of data exists 15,17,18,27 …”
Section: Discussionmentioning
confidence: 99%
“…). Rogers et al demonstrated that the septum is the most reliable segment to measure, minimizing noise and artifacts. When focusing on the smallest segmental T 1 variation part‐interventricular septum, less overlap of the T 1 value was found between the severe overt hypothyroidism group and the control group (Table ).…”
Section: Resultsmentioning
confidence: 99%